Classical and quantum fluid interfaces as simulators for gravity and the early Universe - Barroso Silveira, Vitor (2023)
For the past few decades, gravity and early Universe analogue simulators have been used to experimentally replicate elusive processes and predictions of Quantum Field Theory (QFT) occurring on classical backgrounds of General Relativity using accessible physical systems, such as ultracold atoms, optical devices, and fluid surfaces. The analogies are typically devised by mapping the dynamics of small excitations on the analogue systems to the linear evolution of quantum fields on curved spacetimes. However, the territory of more intricate, interacting QFT problems remains largely unexplored by analogue simulations. This thesis extends the premises of gravity simulators on classical and quantum fluid interfaces to include non-linear processes and discusses suitable measurement schemes required for their development and experimental implementation.